BODIPY star-shaped molecules as solid state colour converters for visible light communications - Chun, H; O'Brien, D; Faulkner, G; Vithanage, D; Manousiadis, P; Sajjad, M; Rajbhandari, S; Orofino, C; Cortizo-Lacalle, D; Kanibolotsky, A; Findlay, N; Faulkner, G; et al. (American Institute of Physics Publishing, 2016)
In this paper, we study a family of solid-state, organic semiconductors for visible light communications. The star-shaped molecules have a boron-dipyrromethene (BODIPY) core with a range of side arm lengths which control the photophysical properties. The molecules emit red light with photoluminescence quantum yields ranging from 22% to 56%. Thin films of the most promising BODIPY molecules were used as a red colour converter for visible light communications. The film enabled colour conversion with a modulation bandwidth of 73 MHz, which is 16 times higher than that of a typical phosphor used in LED lighting systems. A data rate of 370 Mbit/s was demonstrated using On-Off keying modulation in a free space link with a distance of ∼15 cm.